Is empirical research on periodization trustworthy? A comprehensive review of conceptual and methodological issues - Afonso, J.; Nikolaidis, P. T.; Sousa, P.; Mesquita, I. (Journal of Sports Science & Medicine, 2017)
Periodization is a core concept in training. Recently, systematic reviews and meta-analyses have attempted to provide a comprehensive overview of the topic, but theoretical criticisms have arisen with regard to how such research has been conducted. The purpose of the study was to review comprehensively the conceptual and methodological issues surrounding empirical research on periodization in training with human subjects. A search was conducted late in February 2016 on Academic Search Complete, CINAHL Plus, MedicLatina, MEDLINE, PsycINFO, PubMed, Scielo, Scopus, SPORTDiscus and Web of Science. Forty-two randomized or randomized controlled trials were retrieved. Problems emerged in three domains: (a) Conceptually, periodization and variation were applied differently in research, while no empirical research tested predictions concerning direction, timing or magnitude of the adaptations; (b) Study design: More than 95% of papers investigated the `physical` factor (mainly strength). Research on long-term effects was absent (no study lasted more than nine months). Controlling for confounding factors such as nutrition, supplementation and medication was largely ignored; (c) Data analysis was biased as dispersion in responsiveness was ignored when discussing the findings. Overall, research on periodization fails to analyze the conceptual premises proposed by these approaches